The usability of Juniperus virginiana L. as a biomonitor of heavy metal pollution in Bishkek City, Kyrgyzstan - KAŞOĞLU, GÜLTEN; ÖZYİĞİT, İBRAHİM İLKER; SEVEROĞLU, ZEKİ (TAYLOR & FRANCIS LTD, 2015)
Uncontrolled and unplanned urbanization and industrialization due to increase of population and rapid industrial development have created severe environmental problems in Kyrgyzstan during the last few decades. In this study, Juniperus virginiana, a dioecious species, was employed in order to make assessment of the heavy metal pollution rate in the area and of the heavy metal pollution impact on the mineral nutrient status of the plant. For this study, leaf (washed and unwashed) and bark samples of J. virginiana, and its co-located soil samples were collected from eight different stations, all in the capital of Kyrgyzstan, Bishkek, in 2012 vegetation period. The standard procedures were used and the determinations of heavy metal and nutrient element contents (Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Pb and Zn) in all samples were done using inductively coupled plasma-optical emission spectroscopy. According to our measurements, J. virginiana was found to be capable of accumulating a considerable amount of metals and the mineral nutrient uptake pattern was altered because of metal deposition in the plant, which showed a contamination risk in the area.
Keywords: Juniperus virginiana; heavy metal pollution; mineral nutrient status; Bishkek; Kyrgyzstan; PYRACANTHA-COCCINEA ROEM.; HIGHER-PLANTS; GROWTH; LEAD; ACCUMULATION; CADMIUM; PHYSIOLOGY; CHROMIUM; ALUMINUM; COPPER